Experimental Investigation of the Viscosity Parameters Ranges—Case Study of Engine Oils in the Selected Viscosity Grade - Artur Wolak; Grzegorz Zając; Kamil Fijorek; Piotr Janocha; Arkadiusz Matwijczuk (Energies, 2020)
The primary objective of the research was to compare the viscosity parameters of the same viscosity grade engine oils, as declared by the manufacturers, to the actual laboratory measurements. The secondary objective was to briefly investigate (1) what kind of information oil manufacturers provide in the product data sheets of the studied oils, and (2) the potential savings resulting from the use of the energy efficient oils. The study material consisted of 42 selected synthetic engine oils that belong to the 5W-30 viscosity grade. Stabinger SVM 3001 viscometer was used to determine kinematic viscosity at −20 °C, 40 °C, 100 °C and 130 °C. The HTHS (high temperature high shear), CCS (cold cranking simulator), FTIR (Fourier-transform infrared spectroscopy) and GC (Gas Chromatography) measurements were also performed for the samples that had the lowest and the highest kinematic viscosity. Large differences (5–25%) between oil producers’ declarations and the results of laboratory tests were found. Although all of the engine oils tested met the 5W-30 grade standards, the high variability of viscosity measurements needs to be reported. The difference between the oil with the highest and the oil with the lowest kinematic viscosity at −20 °C was 11,804 mm2/s. The outlying temperature-related viscosity profiles were recovered using Mahalanobis distances which identified 16 out of 42 analyzed oil samples as atypical.